Relationship among Creatively, Job Satisfaction and Mental Health in Female Nurses - Y Dehghani; M Dehghani; F Mazaheri Tehrani (Iran University of Medical Sciences, 2013)
Background & Aim : Creativity of the personnel of organizations is one of the major factors in their advancement. T his study aims to determine the relationship between creatively, job satisfaction and mental health in female nurses .   Material & Methods : It was a descriptive correlational study. Among Bushehr's hospitals, three were selected by random cluster sampling method and among the nurses working in these hospitals, 60 married and unmarried female nurses of CCU and ICU were randomly selected and responded to the job satisfaction, general health questionnaires and creativity questionnaire of Abedi. The data were analyzed by Pearson's correlation coefficients for subscales and t tests using SPSS-PC (v.16).   Results : There was a significant negative correlation between anxiety and creativity development . Also there was a significant negative correlation between depressive symptoms and satisfaction with the nature of the work and there was a significant negative correlation between s ymptoms of social dysfunction and satisfaction with pay, satisfaction of the nature of work and job satisfaction total score (p ≥ 0/05 ). Also the Mean difference between married and unmarried female nurses in physical signs and symptoms of anxiety of mental health and initiative and flexibility of creativity was significant (p<0.05) but findings did not show any differences in job satisfaction in married and unmarried female nurses.  Conclusion : According to the findings, promotion of the nurses' levels of function for protection and promotion of their mental health by providing them with training and skills related to creativity and creative strategies and also strategies to increase their job satisfaction is recommended.   Received: 11 May 2013   Accepted: 31 Jul 2013